Behavioral Dynamic Capabilities and Financial Resilience in Digital MSMEs: The Dual Role of Financial Sustainability - Bunyamin Bunyamin; Hanif Mauludin (AIBPM Publisher, 2026)
Digital micro, small, and medium enterprises (MSMEs) operate in highly volatile environments characterized by platform dependency, income fluctuations, and rapid technological change, making financial resilience a critical strategic concern. This study examines the role of forward-looking financial behavior in shaping financial resilience among digital MSMEs in Indonesia, with financial sustainability positioned as both a mediating mechanism and a moderating condition. Grounded in Dynamic Capability Theory (DCT), a quantitative explanatory design was employed using survey data from 180 digital MSME owners selected through purposive sampling, analyzed via Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that forward-looking financial behavior significantly influences financial sustainability (b = 0.737, p 0.001) and financial resilience directly (b = 0.373, p 0.001) and indirectly through financial sustainability (b = 0.275, p 0.001). Financial sustainability also significantly moderates this relationship (b = 0.143, p = 0.007). These findings confirm that financial resilience is built through the interaction of anticipatory behavioral capabilities and sustainable financial conditions, extending DCT into the microfinance domain and underscoring the importance of long-term financial orientation for digital MSME sustainability.